The detrimental crime of abortion: A comparative study between Malaysian law and common law - Mohd Noor, Nor Adila; Aripin, Mohd Ashraf; Jusoff, Kamaruzaman (Academic Journals, 2010)
Although procreation is considered as the most important function of marriage, millions of women use some means of contraception and even resort to abortion. Medical reasons constitute only a small proportion of the actual number of cases and the rest being for social and other reasons. Islam places great value on human life. Any attempt to take it away in any stages is a heinous crime. This research will discuss the different viewpoints of Islamic jurists regarding the legal position of abortion and its punishment under Islamic criminal law. Besides that, this research will also make a comparison with Malaysian and common laws. As a result, the writer found out that abortion should be prohibited as it is a crime against human being and it can only be allowed where the fully trained medical doctor view that the continuance of the pregnancy will endanger the life of the mother.